Graduate Course Experience 2014. A report on the course experience perceptions of recent graduates - Carroll, David (Graduate Careers Australia (GCA), 2015)
Welcome to Graduate Course Experience 2014, the 22nd edition of the annual report into the course experience perceptions of graduates who completed the requirements for a coursework degree from an Australian higher education institution in 2013 and subsequently responded to the 2014 Course Experience Questionnaire (CEQ). In the CEQ, which is administered approximately four months after course completion, respondents are asked to rate the extent to which they agree or disagree with 13 core items constituting two summated rating scales and a single-item overall satisfaction indicator, along with a subset of 36 optional items constituting eight scales, the latter varying based on institutional preference. The facets of the student experience measured by the CEQ are summarised in Table 1. The labels defined in Table 1 are used as abbreviations throughout this report. Although not strictly a scale, the OSI is referred to as such to simplify reporting. Though the CEQ has been administered annually since 1992, two substantial changes to the conduct of the survey in 2010 resulted in a break in the CEQ time series. First, CEQ responses collected by telephone interview were included in the analysis sample for the first time in 2010. In earlier years, only those responses collected online or by paper questionnaire were included. Second, all five points on the Likert-type response format were labelled for the first time in 2010. In earlier years, only the two endpoints were labelled. Both of these changes led to inflated scores relative to previous surveys. Due to this break in the CEQ time series, comparing CEQ results pre and post 2010 is strongly discouraged. This report presents trends in CEQ results since 2010 in the final section. Like the other reports of the 2014 Australian Graduate Survey (AGS), only essential content has been included in order to provide a more accessible report that can be comprehended at a glance. A range of supplementary tables and figures that present CEQ results in much more detail are available from www.graduatecareers. com.au/Research/ResearchReports/ GraduateCourseExperience. These are denoted by letters instead of numbers throughout this report.
Keywords: portraits